Something to Sing About: A Preliminary List of Canadian Staged Dramatic Music Since 1867 - Ingraham, Mary (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2007)
AbstractThe primary aim of this article is to introduce and present a preliminary list of Canadian staged dramatic music composed between 1867 and 2007 as a contribution to a previously under-cultivated field of Canadian cultural activity and research. More than simply an exercise in establishing a repertoire, this article approaches these works as important historical documents that articulate contemporaneous cultural, social, and political values over the past 140 years. Through a discussion of issues raised in determining genre and musical citizenship, the scope, nature, and history of these works lays a foundation for systematic research into this most important Canadian cultural artifact.To facilitate access to what is a substantial body of information, this preliminary list is offered in three formats: 1) alphabetically by composer’s surname; 2) alphabetically by the title of the work; and 3) chronologically by date of completion of the work. Compositions are identified across all formats by a Preliminary Ingraham Number (PIN) comprised of the composer’s surname and the date of completion of the work.